Use of lymphocyte cultures for BrdU replication banding patterns in anuran species (Amphibia) - Kasahara, Sanae [UNESP]; Silva, Ana Paula Zampieri [UNESP]; Gruber, Simone Lilian [UNESP] (Sociedade Brasileira de Genética, 1998)
Descreve-se a padronização da cultura de linfócitos com a finalidade de melhorar as preparações citológicas de espécies de anfíbios anuros. Esta metodologia permite o uso do tratamento pelo BrdU para se obter padrões de bandas de replicação nos cromossomos dessas espécies.

We describe the standardization of lymphocyte culture procedures in order to improve cytological preparations of anuran species. This methodology permits the use of 5-bromodeoxyuridine (BrdU) treatment to obtain replication banding patterns in the chromosomes of these species.